Evaluation of different methods for monitoring incipient carious lesions in smooth surfaces under fluoride varnish therapy - JAINARA MARIA SOARES FERREIRA, MILTON FERNANDO ANDRADE SILVA, ANDRESSA FEITOSA BEZERRA OLIVEIRA, & F (IAPD and Blackwell, 2008)
White spot lesions represent the first clinical observation of demineralization in the enamel and can be regarded as a sign of dental caries.